PENGARUH PEMBERIAN GERAKAN RELAKSASI TERHADAP PENURUNAN LOW BACK PAIN PADA PEKERJA PENENUN ULOS DI GALERY ULOS SIANIPAR MEDAN - Fadlilah Widyaningsih; Anggi Isnani Parinduri; Irmayani .; Santi Jeni Hanrika Simarmata (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2021)
Static positions during work such as sitting for too long can cause exercise loads, stretching muscles, ligament of the spine causing a feeling of comfort in the lower back. One of the non-pharmacological pain management used in pain reduction is by doing relaxation movements. This research wasa quantitative study with a quasi-experimental approach to giving relaxation be used one group pretest posttest. Population of the research is 65 workers with 32 workers as the sample (using purposive sampling technique). The instrument used was numerical rating scale. Data analysis was performed by using univariate and bivariate (using wilcoxon test with Î± = 0,05).The result of this study showed that the p-value is 0,0001. It was indicate that the value of p < 0,05. It could be concluded that the relaxation was that there is an effect of providing relaxation movements to decrease complaints of low back pain in ulos weaver workers in the gallery ulos sianipar medan. A suggestion to the workers is they should do a relaxation when before and after working and using ergonomic position.